Review of Hemidesmus indicus (L.) R. BR - A Comparative Study with Its Substitute Decalephis hamiltonii Wight and Arn - Thillany, P.V.; Sathiyaseelan, V. (Institute of Indigenous Medicine University of Colombo, Rajagiriya Sri Lanka, 2016)
The increasing demand of herbal drug and extinction caused the need of hour to find better substitutes. Hence substitution of drugs made according to their Suvai, Veeryam, and Vipakam. The comparative study was made to ensure that Hemidesmus indicus roots. are lack in use or misidentified and replaced with Decalephis hamiltonii, however it contains potential benefits. The methodology of the study was to compare the potent effects as morphological, organoleptic characters of the plants and roots, phytochemistry, pharmacological activities and actions of both plants relevant to substitution from authentic Siddha texts, Siddha pharmacopoeia, Siddha dictionary, Medicinal plants of Sri Lanka, Wealth of India, Traditional texts, Science journals, Modern scientific findings and web sources. H. indicus (Asclepiadaceae) is a perennial, semi-shrubby, twiner with woody rootstock. Most used part is root. Organoleptic characters of root include Suvai- inippu sirukaippu, Veeriyam-seetham, and Vipakam-inippu. It contains various phytoconstituents as essential oils, small amounts of resin, fatty acids, tannins, saponins, a glycoside and a ketone. The drug has reputation as tonic, alterative, demulcent, diaphoretic, diuretic and blood purifier. It is employed in nutritional disorders, syphilis, chronic rheumatism, gravel and other urinary and skin diseases. Several studies are being carried out towards its activities like analgesic, anti-oxidant, anti-snake venom, anti- hyperlipidaemic, anti-arthrogenic, anti-leprotic, anti-microbial, hepatoprotective and renoprotective. D. hamiltonii (Asclepiadaceae) is a climbing shrub with joined stem, part used of root. Organoleptic characters, Suvai-inippu, Veeriyam-seetham, Vipakam-inippu. As far as its phytochemistry concerned it has volatile principle, aldehyde, inositol, saponins, tannins, a crystalline resin acid, ketonic substance, sterols and resinols. The root is an appetizer and blood purifier. Uses is wound healing, bronchial asthma, fever, intrinsic haemorrhage, ulcer, erysipelas and poisoning. The wide spectrum of pharmacological activitiess that are being studied includes anti-bacterial, anti-ulcer, insecticidal, neuroprotective, hepatoprotective, and gastro protective. The study reveals that D. hamiltonii is substituted for H. indicus; hence this review was carried out to explore the hidden potentials of H. indicus roots and its uses in Siddha towards the benefits of mankind to promote the proper identification and use the certain plant to increase the potency of the drugs.
Keywords: Hemidesmus indicus; Decalephis hamiltonii; Organoleptic characters